Women's support groups : an alternative model for the empowerment of grassroots women - La Fleur, Patrice (WAND St MichaelBB, 1995)
Argues that Caribbean women's groups often alienate working class women by failing to address their concerns and needs. Outlines the objectives, characteristics and principles of an alternative model of women's organising. Describes the actual experience of applying the model in an urban working class community in Guyana.